Oxygen therapy, continuous positive airway pressure, or noninvasive bilevel positive pressure ventilation in the treatment of acute cardiogenic pulmonary edema - Park,Marcelo (2001)
OBJECTIVE: To compare the effects of 3 types of noninvasive respiratory support systems in the treatment of acute pulmonary edema: oxygen therapy (O2), continuous positive airway pressure, and bilevel positive pressure ventilation. METHODS: We studied prospectively 26 patients with acute pulmonary edema, who were randomized into 1 of 3 types of respiratory support groups. Age was 69±7 years. Ten patients were treated with oxygen, 9 with continuous positive airway pressure, and 7 with noninvasive bilevel positive pressure ventilation. All patients received medicamentous therapy according to the Advanced Cardiac Life Support protocol. Our primary aim was to assess the need for orotracheal intubation. We also assessed the following: heart and respiration rates, blood pressure, PaO2, PaCO2, and pH at begining, and at 10 and 60 minutes after starting the protocol. RESULTS: At 10 minutes, the patients in the bilevel positive pressure ventilation group had the highest PaO2 and the lowest respiration rates; the patients in the O2 group had the highest PaCO2 and the lowest pH (p<0.05). Four patients in the O2 group, 3 patients in the continuous positive pressure group, and none in the bilevel positive pressure ventilation group were intubated (p<0.05). CONCLUSION: Noninvasive bilevel positive pressure ventilation was effective in the treatment of acute cardiogenic pulmonary edema, accelerated the recovery of vital signs and blood gas data, and avoided intubation.